Analisis Efektifitas Keputusan DSN-MUI No. 3 Tahun 2000 Berkaitan dengan Dewan Pengawas Syariah di Baitul Mal Wa Tamwil (BMT) Studi Kasus di BMT Bima Magelang - Sofiyah Sofiyah (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
This research is an effort to study and analyze the effectiveness of DSNMUIpolicy No. 3 of 2000 related with DPS in the Syari’ah Financial Institution. The question to answer from this research is whether the DSNMUI policy No. 3 of 2000 related with DPS in LKS is effective to be applied in Baitul Mal Wa Tamwilor not. The result of this study shows that the DSN-MUI policy No. 3 of 2000 related with DPS is not effective yet in the application. This occurs because DPS in BMT is not able to fulfill the requirements of the recruitment of the Syari’ah supervisory board yet, such in the requirements of BMT member that minimally need to have 3 members of DPS and also the requirements of being the Syari’ah supervisory board that need to have certificate of DSN. In other hand, the existence of DSN only fulfills the law of macro financial but not for micro financial yet